The Effects of the Financial Crisison Public-Private Partnerships. (IMF Working Papers; Working Paper ;, 2009)
The paper investigates the impact of the global financial crisis on public-private partnerships (PPPs) and the circumstances under which providing support to new and existing projects is justified. Based on country evidence, cost of and access to finance are found to be the main channels of transmission of the financial crisis, affecting in particular pipeline PPP projects. Possible measures to help PPPs during the crisis include contract extensions, output-based subsidies, revenue enhancements and step-in rights. To limit government's exposure to risk, while preserving private partner's efficiency incentives, intervention measures should be consistent with the wider fiscal policy stance, be contingent on specific circumstances, and be adequately costed and budgeted. Governments should be compensated for taking on additional risk.